2020
DOI: 10.1111/rego.12343
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive governance for the Internet of Things: Coping with emerging security risks

Abstract: The Internet of Things (IoT) is a disruptive innovation known for its socio-economic potential, but also for generating unprecedented vulnerabilities and threats. As a dynamic sociotechnical system, the IoT comprises well-known cybersecurity risks and endemic uncertainties that arise as IoT adoption increases and the system evolves. We highlight the impact of these challenges by analyzing how insecure IoT devices pose threats to both consumer protection and the Internet's infrastructure. While recent regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…This has not always been the case, however, as some of the earliest works on regulation did adopt a temporal perspective which can be usefully deployed to examine the case of disruptive technologies. In his pathbreaking 1955 work, Regulating Business by Independent Commission, for example, Marver Bernstein noted the significance of time in the process of regulatory development and suggested that regulatory agencies tend to follow a set pattern of evolution or lifecycle, one which roughly parallels a human life (Bernstein 1955).…”
Section: Application Of Regulatory Life Cycle Theory To Disruptive Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This has not always been the case, however, as some of the earliest works on regulation did adopt a temporal perspective which can be usefully deployed to examine the case of disruptive technologies. In his pathbreaking 1955 work, Regulating Business by Independent Commission, for example, Marver Bernstein noted the significance of time in the process of regulatory development and suggested that regulatory agencies tend to follow a set pattern of evolution or lifecycle, one which roughly parallels a human life (Bernstein 1955).…”
Section: Application Of Regulatory Life Cycle Theory To Disruptive Technologiesmentioning
confidence: 99%
“…In advancing these arguments, this introductory article brings together two disparate bodies of scholarship: Bernstein's (1955) life-cycle analogy of regulatory development and the "new" design orientation in the contemporary policy sciences to highlight the specific nature of the different kinds of tools that can be used to address contemporary policy challenges. It argues the regulatory challenge facing disruptive technologies centers on how to develop a portfolio of substantive and procedural tools in an asynchronous fashion initially; correcting past problems while developing anticipatory capacities through the early stages of the regulatory life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Coalitions determine the outcomes of the policy process; the actors and their individual attributes determine the coalitions. Brass and Sowell (2021), also in contributing to this issue, examine competing and collaborating actors through an "epistemic communities" perspective.…”
Section: Regulating Emerging Technologiesmentioning
confidence: 99%
“…When confronted with emerging technologies, policy-makers and regulators lack knowledge about what precisely the emerging technology entails, how unwelcome effects of the emerging technology can be tackled, and which sorts of applications of the emerging technologies they should be specifically concerned with (Mandel 2009). Similar issues are confronted across a variety of technological advances in such diverse areas as, for example from cryptoassets (Whitford & Anderson 2020) to nanomaterials and from autonomous systems (Firlej & Taeihagh 2020) to the Internet-of-Things (Brass & Sowell 2021).…”
Section: Introductionmentioning
confidence: 99%